Implications of mating system and pollen dispersal indices for management and conservation of the semi-arid species Prosopis flexuosa (Leguminosae) - Bessega, Cecilia Fabiana (2017)
Recruitment by fencing of semi-arid trees is a common woodland conservation strategy that may haveboth positive and negative implications. Domestic herbivores can act as efficient dispersal seed agentsbut they can also affect the survival and growth of the trees first stages. Prosopis flexuosa (algarrobo)woodlands represent the most important plant community in the Monte region in Argentina and as this resource is affected by deforestation, grazing, natural fires and replacement of natural ecosystems by croplands, in order to protect the ??algarrobo? a reserve had been established. As efficient managementand conservation program depends on the information on population structure and mating system, the objectives of this work were to estimate mating and pollen dispersal patterns in a wild P. flexuosa population from the Ñacuñan fenced to exclude domestic cattle for 40 years. This population is mainlyoutcrosser (tm = 0.996), sensitive to inbreeding depression at seed stage, having relative reduced pollen mediated gene dispersal distance (4.56?20.35 m), which favors inbreeding as a consequence of mating between related individuals. Our results suggest that for ex situ conservation the distance that wouldbe enough to avoid full sib sampling among harvested seed-trees is about 20 m. Collecting seeds from different pods reduce the proportion of full sibs within progeny arrays. For in situ conservation it is important to take into account that forest patches separated by more than 250 m are expected to be isolated,increasing the risk of genetic variability loss, inbreeding increase and population extinction. The results are discussed in reference to the ??algarrobo? management program; while in some case excludingbig mammals from the stands should be advisable, the interaction with long dispersal big herbivores might be considered as a strategy to promote increased outbreeding reducing the rate of mating between related individuals.